On the problems of nonhomogeneous and anisotropic elastic layer-composite plates - Bich, Dao Huy (Vietnam Journal of Mechanics, 1994)
Using the homogenization method problems of nonhomogeneous and anisotropic elastic layer composite plates reduce to the problems of homogeneous and anisotropic elastic plates. The formulae of effective modulus theory determining material behaviors in this cases are given and can be checked by experimental data. Obtained results allow to analyze static and dynamic problems of composite plates by well - know methods.